Cross-Cultural Insights into Phatic Communication: Indonesian and Australian Student Interactions - Ilmi, Assayyidah Bil Ichromatil; Degaf, Agwin (Deskripsi Bahasa, 2024)
Phatic communication, a widespread yet often unnoticed language phenomenon, primarily serves to maintain social interactions rather than convey substantive information. This study investigated the use of phatic expressions among Indonesian and Australian students, examining how cultural backgrounds and social contexts influence their communication styles. Using a Discourse Completion Task (DCT) with both qualitative and quantitative methods, this research revealed significant differences between the two groups. Australian students frequently used phatic speech to initiate conversations, provided comfort, and expressed empathy, emphasizing respect and interpersonal connection. In contrast, Indonesian students tended to use phatic expressions to promote social harmony, engage in casual discourse, and offer interpersonal support, often focusing on group cohesion. Social variables, such as social status and distance, played a critical role in shaping the choice of phatic functions and forms, with both groups adapting their communication strategies based on these factors. The findings highlight the intricate relationship among culture, social dynamics, and language in phatic communication, offering a nuanced understanding that can enhance intercultural interactions, minimize misunderstandings, and improve communication effectiveness in multicultural settings. This research underscores the importance of considering cultural and social contexts when analyzing language use, contributing valuable insights for educators, linguists, and communication professionals aiming to foster more effective and harmonious interactions across diverse cultural landscapes.